Resistance of stored bean varieties to Acanthoscelides obtectus (Coleoptera : Bruchidae) - Baldin, Edson Luiz Lopes [UNESP]; Lara, Fernando Mesquita [UNESP] (Wiley-Blackwell, 2008)
During bean seed storage, yield can be lost due to infestations of Acanthoscelides obtectus Say, the bean weevil. The use of resistant varieties has shown promising results in fighting these insects, reducing infestation levels and eliminating chemical residues from the beans. The expression of resistance to A. obtectus in bean varieties is frequently attributed to the presence of phytohemagglutinins, protease inhibitors and alpha-amylase, and especially to variants of the protein arcelin, which reduce the larval viability of these insects. To evaluate the effect of bean seed storage time on the resistance expression of bean varieties to A. obtectus, tests with seeds of three ages (freshly-harvested, 4-month-old, and 8-month-old) were conducted in the laboratory, using four commercial varieties: Carioca Pitoco, Ipa 6, Porrillo 70, Onix; four improved varieties containing arcelin protein: Are. 1, Arc.2, Arc. 3, Arc.4; and three wild varieties also containing arcelin protein: Arc. IS, Arc.3S, and Arc. 5S. The Arc.5S, Arc. IS, and Arc.2 varieties expressed high antibiosis levels against the weevil; Arc. I and Arc3S expressed the same mechanism, but at lower levels. The occurrence of oviposition non-preference was also observed in Arc.5S and Arc. IS. The Arc.3 and Arc. 4 varieties expressed low feeding non-preference levels against A. obtectus. The expression of resistance in arcelin-bearing, wild or improved varieties was affected during the storage of seeds, and was high under some parameters but low in others. The results showed that addition of chemical resistance factors such as protein arcelin via genetic breeding may be beneficial in improving the performance of bean crops.
Keywords: antibiosis; antixenosis; bean weevil; host plant resistance; Phaseolus vulgaris